The trip to Italy [videorecording (DVD)] - Winterbottom, Michael; Coogan, Steve; Brydon, Rob, 1965- (MPI Home Video, 2014)
Steve Coogan and Rob Brydon are on an all-expenses-paid trip for the Observer. Their tough assignment is to drive through beautiful Italian country, eat lavishly, and stay in exquisite small hotels, all so that one or the other can write high-toned culinary drivel for the paper.